DAMPAK GAME ONLINE TERHADAP HASIL BELAJAR SISWA KELAS V: KAJIAN FENOMONOLOGI DI UPT SD NEGERI 064037 MEDAN TEMBUNG - Gabyana Margaretha Marbun; Dody Feliks Pandimun Ambarita; Eva Betty Simanjuntak; Albert Pauli Sirait; Edizal Hatmi; Charles Fransiscus Ambarita (STKIP Subang, 2025)
This study aims to determine the impact of online gaming on the learning outcomes of fifth-grade students at UPT SD Negeri 064037 Medan Tembung in the 2024/2025 academic year. This research employs a descriptive method with a qualitative approach. The research subjects were 30 fifth-grade students. The instruments used in this study was an online gaming questionnaire using a Likert scale, interviews, and documentation of students’ learning outcome scores. The results of the study indicate that more than half of the students showed a tendency to neglect school assignments (55.83%), less than half experienced physical and psychological impacts (45%), the majority experienced impacts of online gaming on learning motivation positive impacts of online gaming (22.3%), and more than half experienced negative impacts of online gaming (55%).